First Report of Lasiodiplodia theobromae Causing Stem Brown Rot of Loquat in China - Kong, Qiong (Plant disease, 2023)
Loquat (Rhaphiolepis biabas, heterotypic synonym: Eriobotrya japonica) is an important edible and medicinal plant that is widely cultivated on 133 thousand hectares (recorded in 2022) in China. A stem brown rot was observed on young and old trees in Mengzi city (23°23' N; 103°23' E), Yunnan Province, southwest China, during October 2014 and September 2021. Incidence ranged from 20% of trees in surrounding plantations to 50% incidence of a 160 tree orchard that was the focal point of the disease survey. Circular brown lesions occurred initially on the stems and gradually covered all the epidermis of the stem, leading to irregular dents within the bark that developed a dark brown powdery appearance (Fig.1A). Larger lesions affected vascular tissues, causing diseased trees to wither and die. Diseased tissues were surface-disinfected in a 5% sodium hypochlorite solution for 3 min, rinsed three times with sterile distilled water, placed on potato dextrose agar (PDA), and incubated in the dark at 28°C. Twenty samples were collected for tissue isolation, and 11 isolates were single-spored on water agar. In culture, the colonies on PDA were white to dark-gray, velvet, with dense hyphae, diameter 7.64 cm after 5 days. After 18 days, spherical or subglobose pycnidia were developed and semi-buried in medium, their walls were thicker and dark-brown, which were black particles surrounded by gray-black hyphae. Conidiogenous cells were hyaline, cylindrical, holoblastic, slightly swollen at the base, with rounded apex. Conidia were initially hyaline and aseptate with elliptic or ovate shape, becoming dark brown with a single septate and developing longitudinal striations along thick walls at maturity. Conidia dimensions varied from 8.0 to 12.2 × 3.8 to 6.1μm (n=50) (Fig.1D). The morphological characteristics of eleven isolates were consistent with the description of Lasiodiplodia theobromae (Alves et al. 2008). Further confirmation was also determined by sequencing the internal transcribed spacer (ITS), β-tubulin genes, partial translation elongation factor-1α (TEF-1α) (White et al. 1990, Carbone et al. 1999, Glass et al.1995). The isolate LSB-1 was selected for DNA sequence analysis. Based on BLASTn analysis, ITS sequences (OM617921) had 98.3% similarity with L. theobromae CBS164.96 (accession AY640255), CBS124.13(accession DQ458890), CAA006 (accession DQ458891) and CBS111530 (accession EF622074), β-tubulin sequences (OM643838) showed 99.1% similarity with L. theobromae accessions EU673110. The TEF-1α (OM643839) had 99.0% identity with L. theobromae accession EF633054. The isolate LSB-1 clustered on the same clade with other L. theobromae. Pathogenicity testing of isolate LSB-1, LSB-2, LSB-3 was conducted by inoculating the stems of l-year-old seedlings growing in pots. The epidermis at the inoculation site, 15-20 cm below the crown, was wiped with 75% alcohol cotton ball, washed three times with sterile water, and then punctured (5mm diameter) with sterile inoculation needle. A 5mm block of each isolate cultured on PDA for seven days was attached to the inoculation site. Controls were inoculated with sterile PDA blocks. The inoculation area was covered with polyethylene cling film. All inoculated seedlings were kept in controlled greenhouse at 27°C with 80% relative humidity under natural daylight conditions, and watered weekly. Each treatment was repeated three times. Eight days after inoculation, all diseased plants showed dark brown discoloration at the point of inoculation (Fig. 1G) with the bark at the inoculation site gradually raising as the disease progressed. Thirty days after inoculation, all inoculated seedlings produced typical symptoms, whereas the control seedlings remained healthy. Fungal isolates were only recovered from symptomatic stems and were morphologically identical to L. theobromae, completing Koch's postulates. According to the relevant literature, Lasiodiplodia theobromae has a broad host range, causing numerous diseases, including canker and dieback of branch (Aguilera-Cogley et al., 2021), panicle blight (Mahadevakumar et al, 2022), root rot (Abd-El Ghani and Fatouh, 2005), fruit rot(Freire et al., 2011) in diverse geographical regions. To our knowledge, this is the first report of L. theobromae causing stem brown rot of loquat in China and provides a foundation for further study of the epidemiology and integrated management of this disease